Transformation of Dunaliella salina by Agrobacterium tumefaciens for the Expression of the Hemagglutinin of Avian Influenza Virus H5 - Inkar Castellanos-Huerta; Gabriela Gómez-Verduzco; Guillermo Tellez-Isaias; Guadalupe Ayora-Talavera; Bernardo Bañuelos-Hernández; Víctor Manuel Petrone-García; Gilberto Velázquez-Juárez; Isidro Fernández-Siurob (Microorganisms, 2022)
Avian influenza (AI) is one of the main threats to the poultry industry worldwide. Vaccination efforts are based on inactivated, live attenuated, and recombinant vaccines, where the virus hemagglutinin (HA) is the main component of any vaccine formulation. This study uses Dunaliella salina to express the AIV HA protein of an H5 virus. D. salina offers a system of feasible culture properties, generally recognized as safe for humans (GRAS), with N-glycosylation and nuclear transformation by Agrobacterium tumefaciens. The cloning and transformation of D. salina cells with the H5HA gene was confirmed by polymerase chain reaction (PCR). SDS-PAGE and Western blot confirmed HA5r protein expression, and the correct expression and biological activity of the HA5r protein were confirmed by a hemagglutination assay (HA). This study proves the feasibility of using a different biological system for expressing complex antigens from viruses. These findings suggest that a complex protein such as HA5r from AIV (H5N2) can be successfully expressed in D. salina.